Development of a Method for Diagnosing Injectors of Diesel Engines - Ildar Gabitov; Andrei Negovora; Shamil Nigmatullin; Arseny Kozeev; Mahmut Razyapov (Communications - Scientific letters of the University of Zilina, 2021)
The purpose of this study was to improve the diagnostics efficiency of modern diesel engine injectors with electronic controls. Experimental studies, performed using certified specialized equipment of injectors’ manufacturers and standard software packages for data analysis, made it possible to prove adequacy of theoretical research and get results that are more accurate. Those results contribute to development of a software product that allows identifying a particular faulty element during the defective injector’s operation by using mathematical processing of the diagnostic data obtained when testing the injector. Thus, the time spent to repair the fuel injection system reduces. The developed software product also helps to predict the remaining injector’s operational life and prevent possible technical failures during operation.